2021
DOI: 10.7759/cureus.12706
|View full text |Cite
|
Sign up to set email alerts
|

Sideburns Obesity Syndrome: Is Sideburn Fat the Window to the Heart?

Abstract: Despite significant advancements in cardiovascular diagnostic technology, physical examination signs remain credible diagnostic indicators of coronary artery disease. Here, we report a case of a 50-year-old male patient with premature coronary artery disease associated with a novel physical sign of bilateral symmetrical bulging of the sideburn areas of the face. The sideburns correspond anatomically to the buccal fat pad which is composed of visceral adipose tissue. Visceral obesity is an established risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The population-based study of coronary heart disease, among 1,237 American Japanese men aged 50-74, found that "creases are prevalent in fat men" without significant correlation with coronary artery disease (CAD) [12]. In January of 2021, the author of the current article reported an association between visceral obesity of the BFP and premature coronary disease and termed the condition "sideburns obesity syndrome" [13].…”
Section: Introductionmentioning
confidence: 99%
“…The population-based study of coronary heart disease, among 1,237 American Japanese men aged 50-74, found that "creases are prevalent in fat men" without significant correlation with coronary artery disease (CAD) [12]. In January of 2021, the author of the current article reported an association between visceral obesity of the BFP and premature coronary disease and termed the condition "sideburns obesity syndrome" [13].…”
Section: Introductionmentioning
confidence: 99%